2018
DOI: 10.1037/bne0000229
|View full text |Cite
|
Sign up to set email alerts
|

Retrosplenial cortex has a time-dependent role in memory for visual stimuli.

Abstract: Although the retrosplenial cortex (RSC) is critically involved in spatial learning and memory, it appears to have more selective contributions to learning and memory for discrete cues. For example, damage to the RSC does not impair Pavlovian delay fear conditioning to a discrete auditory cue (e.g., tone), when RSC manipulation occurs just prior to, or shortly after, conditioning. In contrast, when lesions of the RSC occur following a substantial retention interval (e.g., 28 days), the RSC is necessary for retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…1F, G). Previous studies improved that the retrosplenial granular cortex (RSG) has dense connections with social-related brain regions (Vogt, 2019a) and integrates different kinds of sensory information, including auditory, visual and olfactory (Jiang et al, 2018;Todd et al, 2016). These results raise our hypothesis that RSG may regulate social behavior.…”
Section: Involvement Of the Rsg In Social Interactionmentioning
confidence: 88%
See 1 more Smart Citation
“…1F, G). Previous studies improved that the retrosplenial granular cortex (RSG) has dense connections with social-related brain regions (Vogt, 2019a) and integrates different kinds of sensory information, including auditory, visual and olfactory (Jiang et al, 2018;Todd et al, 2016). These results raise our hypothesis that RSG may regulate social behavior.…”
Section: Involvement Of the Rsg In Social Interactionmentioning
confidence: 88%
“…Anatomically, the retrosplenial cortex(RSC) reciprocally connected with many brain regions, including the hippocampus, thalamus, visual cortex, auditory cortex, motor cortex, and prefrontal cortex (Jiang et al, 2018;Todd et al, 2016). Most of them are key brain regions for social behavior, which is indicated by RSC's function, such as spatial navigation (11), emotion, learning and memory, and high cognitive functions: imagination.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the retrosplenial cortex receives visual information directly from the geniculostriate and tecto-cortical visual systems and shares reciprocal connections with the parietal and parahippocampal cortices ( Van Groen & Wyss, 1990 , 1992a , 1992b ; Van Groen & Wyss, 2003 ). Indeed, research has shown that the rat retrosplenial cortex contributes to learning about stimuli that are not explicitly spatial ( Bussey, Muir, Everitt, & Robbins, 1996 ; Hindley, Nelson, Aggleton, & Vann, 2014 ; Jiang, DeAngeli, Bucci, & Todd, 2018 ; Keene & Bucci, 2008a , 2008b ; Kwapis, Jarome, Lee, & Helmstetter, 2015 ; Miller et al, 2014 ; Nelson, Hindley, Haddon, Vann, & Aggleton, 2014 ; Robinson, Keene, Iaccarino, Duan, & Bucci, 2011 ; Robinson et al, 2014 ; Smith, Freeman, Nicholson, & Gabriel, 2002 ; Smith, Miller, & Vedder, 2018 ).…”
mentioning
confidence: 99%
“…Recent behavioral studies reported that the RSC is also implicated in storing and expression or retrieval of remote memory of nonspatial cues associated with reinforcement (Todd et al, 2016; Jiang et al, 2018; Fournier et al, 2019a). Theta oscillation is implicated in neurophysiological mechanisms for retrieval of remote memory: it reflects memory search and information transfer between the hippocampal formation and the cortical areas such as the RSC (Hasselmo, 2002; Fell and Axmacher, 2011; Burke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%